2014
DOI: 10.1177/0091026014533898
|View full text |Cite
|
Sign up to set email alerts
|

Moral Identity as a Moderator of the Effects of Organizational Injustice on Counterproductive Work Behavior Among Chinese Public Servants

Abstract: Despite the considerable research to investigate the influence of organizational injustice on employees' counterproductive work behaviors (CWB), relatively little attention has been paid to the role of moral identity. In the present study, we posit that people's moral identity serves as a buffering factor between organizational injustice and CWB among Chinese public servants. Consistent with the hypotheses, survey results showed that organizational justice and moral identity interacted to influence Chinese pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…The results of this study support the previous studies such as researches conducted by Fox, et al (2001), Devonish & Greenidge (2010), Mingzheng, et al (2014), Novrianti & Claudius (2014), and Rauf (2015). Abas, et al (2016) in his research explained that Perceived Organizational Support (POS) and Counter Productive Behavior have interaction relations that affect each other.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study support the previous studies such as researches conducted by Fox, et al (2001), Devonish & Greenidge (2010), Mingzheng, et al (2014), Novrianti & Claudius (2014), and Rauf (2015). Abas, et al (2016) in his research explained that Perceived Organizational Support (POS) and Counter Productive Behavior have interaction relations that affect each other.…”
Section: Discussionsupporting
confidence: 92%
“…But if employees feel organizational injustice, they will display negative attitudes and behavior outcomes (Adams, 1965 ; Greenberg, 1990 , 1993 , 2001 ; Li and Shi, 2003 ; Pi, 2006 ; Ceylan and Sulu, 2011 ; Mingzheng et al, 2014 ; Chih et al, 2016 ). These results were in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Min et al ( 2014 ) suggested that perceived injustice during work is significantly associated with an increased risk of occupational disease and absenteeism for Korean employees. Mingzheng et al ( 2014 ) suggested that organizational justice is negatively correlated with counterproductive work behavior among Chinese public servants. Finding from Michel and Hargis ( 2017 ) showed that procedural injustice motivates deviant behavior in the workplace.…”
Section: The Theoretical Background and Hypothesismentioning
confidence: 99%
“…Thus, employees might try to reinstate equity by displaying negative behavior as a response to their unfulfilled psychological contract. Mingzheng et al (2014) found that perceptions of organizational justice were negatively correlated with DWB in a sample of Chinese civil servants. Similarly, Quratulain and Khan (2015b) demonstrated that resigned satisfaction, a psychological state somehow similar to PCB, was found to be positively related with withdrawal behavior (a type of deviant behaviors) in a sample of Pakistani public sector managers.…”
Section: Pcb and Dwbmentioning
confidence: 92%
“…The focus of current study is on the behavioral reactions of employees in the form of DWB which are defined as intentional behavior that spoils organizational values and norms, simultaneously damaging the well-being of the organization and its members (Robinson & Bennett, 1995). There is ample evidence in literature which suggests that organizational unfairness and a lack of merit-based rewards in the workplace can result in DWB (Mingzheng, Xiaoling, Xubo, & Youshan, 2014). The unethical practices of organizational cronyism have a different impact on crony favored and nonfavored employees (Khatri & Tsang, 2003).…”
Section: Hypotheses Developmentmentioning
confidence: 99%